Trajectories of child free sugars intake and dental caries - a population-based birth cohort study - Ha, Diep; Nguyen, Huy; Bell, Lucinda; Devenish-Coleman, Gemma; Thomson, W.M.; Manton, D.; Leary, S.; Scott, Jane; Spencer, A.J.; Do, Loc (Elsevier, 2023)
Objectives: To investigate the association between trajectories of free sugars intake during the first five years of life and dental caries experience at five years. Methods: Data from the SMILE population-based prospective birth cohort study, collected at one, two and five years old, were used. A 3-days dietary diary and food frequency questionnaire were used to estimate free sugars intake (FSI) in grams. The primary outcomes were dental caries prevalence and experience (dmfs). The Group Based Trajectory Modelling method was used to characterize three FSI trajectories (‘Low and increasing’; ‘Mod erate and increasing’; and ‘High and increasing’), which were the main exposures. Multivariable regression models were generated to compute adjusted prevalence ratios (APR) and rate ratios (ARR) for the exposure, controlling for socioeconomic factors. Results: The prevalence of caries was 23.3%, with a mean dmfs of 1.4, and a median of 3.0 among those who had caries. There were clear gradients of caries prevalence and experience by the FSI trajectories. The ‘High and increasing’ had an APR of 2.13 (95%CI 1.23-3.70) and ARR of 2.77 (95%CI 1.45-5.32) against the ‘Low and increasing’. The ‘Moderate and increasing’ group had intermediate estimates. A quarter of the caries cases could have been prevented if the whole study sample had been in the ‘Low and increasing’ FSI trajectory. Conclusion: A sustained, high trajectory of FSI from a young age was positively associated with child dental caries. Measures to minimise consumption of free sugars must commence early in life. Clinical significance: The study has provided high level evidence to inform clinicians’ decisions in promoting a healthy dietary pattern for young children.